Enterprise Resource Planning (ERP) Implementation in a Sub-Saharan African Nation: An Empirical Test of Competing Models and Theories - Asamoah, David (2018)
A Thesis submitted to the Department of Information Systems and Decision Sciences, School of Business, College of Art and Social Sciences in partial fulfillment of the requirements for the degree of Doctor of Philosophy.